2010
DOI: 10.1103/physreve.82.011904
|View full text |Cite
|
Sign up to set email alerts
|

Evolution models with lethal mutations on symmetric or random fitness landscapes

Abstract: We calculate the mean fitness for evolution models, when the fitness is a function of the Hamming distance from a reference sequence, and there is a probability that this fitness is nullified (Eigen model case) or tends to the negative infinity (Crow-Kimura model case). We calculate the mean fitness of these models. The mean fitness is calculated also for the random fitnesses with logarithmic-normal distribution, reasonably describing sometimes the situation with RNA viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…To summarize-recent studies and experiments [6,24,27,28,[30][31][32][33]38] show that evolutionary trajectories in realistic and correlated fitness landscapes may pass through fitness valleys due to epistatic interactions or through long-range connections due to multiple mutations in a single step. Also, lethal mutations would lead to infeasible paths.…”
Section: Various Paths Suggested By Experimental Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize-recent studies and experiments [6,24,27,28,[30][31][32][33]38] show that evolutionary trajectories in realistic and correlated fitness landscapes may pass through fitness valleys due to epistatic interactions or through long-range connections due to multiple mutations in a single step. Also, lethal mutations would lead to infeasible paths.…”
Section: Various Paths Suggested By Experimental Evolutionmentioning
confidence: 99%
“…It is observed that many point mutations are responsible for the lethality of an individual [28,[33][34][35][36]. These lethal genotypes are not connected with other viable genotypes through an evolutionary path due to natural selection [4,5,37].…”
Section: Various Paths Suggested By Experimental Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Главное наше допущение -однопиковая функции приспособленности, применяемая биологами как грубое приближение к реальности [Gupta, Dixit, 2015]. Но те же математические результаты остаются корректными для случайной функции приспособленности [Kirakosyan, Saakian, Hu, 2010], которая довольно распространена в моделях вирусологии [Sanjuan, Moya, Elena, 2004]. Результат М. Казарян, Т. С. Якушкина, Д. Б. Саакян (13), точечная -численным более ранней работы [Saakian, Hu, 2004] получил широкое применение к различным задачам эволюционной биологии.…”
Section: заключениеunclassified
“…In smooth fitness landscapes, the steady-state distributions of the Crow-Kimura and Eigen models can be mapped to each other. In the large genome limit, the Crow-Kimura model is equivalent to a discrete-time Eigen model 33 and is very close to branching processes. Moreover, the Wright-Fisher model 34 35 for large populations can be mapped to a discrete-time Eigen model 33 .…”
mentioning
confidence: 99%